Why radicalization fails: barriers to mass casualty terrorism - Simi, Pete (Terrorism and political violence, 2020)
Few issues have garnered as much attention in recent years as the topic of violent extremism (VE). Although substantial attention has been devoted to investigating the radicalization process, few scholars have examined the obstacles that hinder VE radicalization. Based on in-depth life history interviews, the current study examines five types of barriers that hinder radicalization toward mass casualty violence (MCV): mass casualty violence as counter-productive; preference toward interpersonal violence, changes in focus and availability; internal organizational conflict; and moral apprehension. In general, we address each barrier’s unique contribution to hindering the likelihood of MCV. Finally, we discuss how our findings could be used as part of initiatives aimed at countering violent extremism (CVE).